Investigating Effects of IR-780 in Animal Models of B16-F10 Melanoma: New Approach in Lung Metastasis - Evelyn de Andrade Salomão; Valter Aragão do Nascimento; Caio Fernando Ramalho de Oliveira; Iandara Schettert Silva; Rita de Cássia Avellaneda Guimarães; Danielle Bogo (Molecules, 2023)
IR-780 is a fluorescent marker, photostable and non-toxic, and is widely used in tumor targeting; however, studies on the impact of IR-780 in animal models of B16-F10 melanoma are scarce in the literature. Therefore, this study aims to analyze behavior of this marker in melanoma cells using in vitro and in vivo analyses with fluorescence microscopy to conduct an analysis of cell culture, and an in vivo imaging system for an analysis of cell culture, tumor targeting on animals, and organ examination. In vitro analysis showed that B16-F10 cells at a concentration of 2 × 105 cells.plate−1 allowed a better visualization using 20 μM of IR-780. Furthermore, the location of IR-780 accumulation was confirmed by its fluorescence microscopy. Through in vivo studies, fluorescence was not observed in subcutaneous nodules, and it was found that animals that received intraperitoneal injection of B16-F10 cells presented ascites and did not absorb IR-780. Additionally, animals exhibiting lung metastasis showed fluorescence in ex vivo lung images. Therefore, use of the IR-780 marker for evaluating the progression of tumor growth did not demonstrate efficiency; however, it was effective in diagnosing pulmonary metastatic tumors. Although this marker presented limitations, results of evaluating pulmonary involvement through ex vivo fluorescence imaging were determined based on intensity of fluorescence.